Obstetric medicine - L. Balbi; V. Donvito; A. Maina (Italian Journal of Medicine, 2013)
BACKGROUND Obstetric assistance made major advances in the last 20 years: improved surgical technique allows quicker caesarean sections, anaesthesiology procedures such as peripheral anaesthesia and epidural analgesia made safer operative assistance, remarkably reducing perioperative morbidity and mortality, neonatology greatly improved the results of assistance to low birth weight newborns. A new branch of medicine called “obstetric medicine” gained interest and experience after the lessons of distinguished physicians like Michael De Swiet in England. All together these advances are making successful pregnancies that 20 years ago would have been discouraged or even interrupted: that’s what we call high risk pregnancy. High risk of what? Either complications of pregnancy on pre-existing disease or complications of pre-existing disease on pregnancy. Nowadays, mortality in pregnancy has a medical cause in 80% of cases in Western countries (Confidential Enquiry on Maternal Deaths, UK, 2004). DISCUSSION The background is always changing and we have to take in account of: increase of maternal age; widespread use of assisted fertilization techniques for treatment of infertility; social feelings about maternity desire with increasing expectations from medical assistance; immigration of medically “naive” patients who don’t know to have a chronic disease, but apt and ready to conceive; limited knowledge of feasibility of drug use in pregnancy which may induce both patients and doctors to stopping appropriate drug therapy in condition of severe disease. Preconception counseling, planning the pregnancy, wise use of drugs, regular follow-up throughout the pregnancy and, in selected cases, preterm elective termination of pregnancy may result in excellent outcome both for mother and foetus. CONCLUSIONS Highly committed and specifically trained physicians are required to counsel these patients and to plan their treatment before and during pregnancy.